The Effect of Carbohydrate Diets on Amateur Runners’ Performance - Rosa, Erika S; Goston, Janaina L; Abreu, Wilson C; Silva, Sandro Fernandes da (Journal of Sports Research, 2022)
Carbohydrate (CHO) consumption contributes to minimizing muscular and hepatic glycogen stores during long-distance running. Coinciding with fatigue onset and performance decline, a decrease in the amount of carbohydrates affects performance in runners adversely. Accordingly, the effect of three CHO diets (30%, 60%, and 80%) were each analyzed for seven days on amateur runners’ 5 km performance. Ten amateur male runners (36.4 ± 12.7 years, 175 ± 4.5 cm, 70.2 ± 6.31 kg) performed a pretest and three running tests. Body mass was assessed before and after exercise. Pacing and time were measured for each kilometer in all the research phases. Two-way Anova repeated measures were employed to analyze the data. In the pretest, the CHO intake results revealed 4.20 ± 1.86 g/kg. In the 30% diet, CHO consumption was 30.80 ± 1.07% or 2.20 ± 0.42 g/kg; in the 60% diet, 59.34 ± 0.82% or 4.24 ± 0.82 g/kg; and in the 80% diet, 77.79 ± 1.00 % or 5.56 ± 4.15 g/kg. All analyses showed no significant difference among the CHO diets. However, in the 80% protocol, time improved by 2.30% in comparison to the 30% diet and the pretest. Our results revealed that changing dietary CHO in comparison to a runner’s usual intake did not improve their athletic performance.